Management practices during the renewal year affect the carbon balance of a boreal legume grassland - Li, Yuan; Korhonen, Panu; Kykkänen, Sanna; Maljanen, Marja; Virkajärvi, Perttu; Shurpali, Narasinha J. (Frontiers in Sustainable Food Systems, 2023)
Evaluating the net ecosystem carbon balance (NECB) of legume based grasslands is critical for optimising grassland management and assessing the sustainability of milk and beef industries that rely on grasslands. We measured the NECB of a legume grassland in eastern Finland from May 2017 to May 2020, covering the entire three-year rotation cycle. Results showed that daily net ecosystem carbon dioxide (CO2) exchange (NEE) patterns during the growing seasons varied with photosynthetically active radiation, temperatures, climatic stress (vapour pressure deficit, VPD) and grassland management practices such as fertilization, grass cutting and grassland renovation. Long winters were characterised by sustained, low CO2 emissions. The grassland showed interannual variability fixing 220 g C m-2 as NEE in the first year (May 2017 – May 2018), while it sequestered 334 g C m-2 from June 2018 to May 2019. Nevertheless, the grassland fixed more C during this year than during the previous year owing to an early start (by 15 days) of the growing season and favourable conditions (optimum temperature, high soil moisture and low VPD) for high photosynthetic activity before the first grass cut in this year. The grassland was treated with glyphosate in September and ploughed in October 2018 and left bare to overwinter. It was reseeded in June 2019. Thus, the last year of the rotation period from June 2019 to May 2020 was characteristic of the renewal of the grassland rotation. During this period, the ecosystem lost 146 g C m-2 to the atmosphere. Moreover, this study aimed to quantify the effects of mineral nitrogen fertiliser or digestate residue addition on the NECB of this legume grassland. Segregating the data based on wind direction did not reveal any noteworthy differences in NEE between the two treatments, and light response curves from the two treatments in different years were similar. Thus, we infer that more emphasis should be given to developing climate-friendly renovation management that maximises the length of the photosynthetic period. The boreal legume grasslands added with organic fertilizer have the potential to sequester C and thus help sustain ecosystem services.